Republiken als Blaupause: Venedig, die Niederlande und die Eidgenossenschaft im Reformdiskurs der Frühaufklärung - Weeber, Urte (Ancien Régime, Aufklärung und Revolution, 2016)
"Should refugees be regarded as an important economic factor? Can a federal commonwealth act in a politically effective manner? How can freedom and stability be guaranteed in the European power nexus? Contemporary republics incorporated the perspectives of political reformist thinking during the early Enlightenment. Across Europe, they became the focus of a new rational analysis, which sought to sound out possibilities for the present and future"--Provided by publisher
"...unter dem Titel: Die Zukunft gestalten. Venedig, die Vereinigten Provinzen der Niederlande und die Eidgenossenschaft als Fluchtpunkte des Sagbaren in einem politischen Reformdiskurs der Frühaufklärung im Frühjahr 2014 als Dissertation an der Philosophischen Fakultät der Universität Heidelberg angenommen" - (Vorwort Seite V)
Quellen- und Literaturverzeichnis: Seite [485]-528
Keywords: Venice (Italy) -- Politics and government -- 1508-1797; Netherlands -- Politics and government -- 1648-1795; Europe -- Politics and government -- 1648-1789; Switzerland -- Politics and government -- 1648-1789; Hochschulschrift; Geschichte 1650-1750; Aufklärung; Konstrukt; Republik; Niederlande; Schweiz; Venedig